2008
DOI: 10.1002/mrm.21751
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐body imaging at 7T: Preliminary results

Abstract: The objective of this study was to investigate the feasibility of whole-body imaging at 7T. To achieve this objective, new technology and methods were developed. Radio frequency (RF) field distribution and specific absorption rate (SAR) were first explored through numerical modeling. A body coil was then designed and built. Multichannel transmit and receive coils were also developed and implemented. With this new technology in hand, an imaging survey of the "landscape" of the human body at 7T was conducted. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
270
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 254 publications
(271 citation statements)
references
References 16 publications
1
270
0
Order By: Relevance
“…This has both advantages and disadvantages. Recent studies have shown that homogeneous transmit fields can be produced using transmit arrays and sophisticated B 1 shimming routines (29). Although this represents the optimum strategy, it does require hardware that is not yet standard on most commercial MRI scanners, and it currently necessitates the development of sophisticated hardware and software interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This has both advantages and disadvantages. Recent studies have shown that homogeneous transmit fields can be produced using transmit arrays and sophisticated B 1 shimming routines (29). Although this represents the optimum strategy, it does require hardware that is not yet standard on most commercial MRI scanners, and it currently necessitates the development of sophisticated hardware and software interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…For measurements inside the MR imager, the checkerboard phantom was placed centrally in a custom-built 8-channel head coil (13), so that the checkerboard pattern was visible in the axial slice. To provoke strong B 1 inhomogeneities, the checkerboard phantom was inserted into a water-filled canister of 15 Â 15 Â 20 cm 3 . For comparison with a nearly homogeneous transmit field, the experiment was repeated without the water-filled canister.…”
Section: Contrast Measurementsmentioning
confidence: 99%
“…At higher field strengths, an increased signal-to-noise ratio and new contrasts can be obtained; however, high static field strengths of 7 T and above lead to severe radiofrequency (RF) homogeneity problems (1,2), because the operational frequency is proportional to the static field strength, and hence, the wavelength is shortened. Especially, whole-body imaging at 7 T and higher is therefore challenging (3). Multichannel transmit approaches to tackle these problems have been proposed in the literature.…”
mentioning
confidence: 99%
“…MRI accidents are listed as number 9 of the top 10 risks in modern medicine [1][2]. With the advent of (ultra)high field MR systems [3][4][5][6][7][8][9][10][11][12][13][14] this risk, which is commonly known as the missile or projectile effect is even more pronounced. These projectiles usually consist of common office and hospital items that contain a fair amount of ferromagnetic metal including for example hospital beds, intra venous poles, oxygen tanks, and conventional ECG devices used for patient monitoring, computer displays, ventilator etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent designs have typically been laid out as strip line elements on rigid or semiflexible frames [7]. A strategy employing small magnetic field alert sensors which can be attached to ferromagnetic objects that are commonly used in a clinical environment is conceptually appealing for the pursuit of reducing the risk of ferromagnetic projectile accidents.…”
Section: Introductionmentioning
confidence: 99%